'NOTCHing up' the In Vitro Production of Dendritic Cells. Issue 10 (October 2018) - Guilliams, Martin; Scott, Charlotte L.
Abstract : Two studies show that adding NOTCH ligands to Flt3L cultures increases the yield of cDC1s from mouse and human progenitors. Moreover, these NOTCH-DCs more closely resemble in vivo DCs transcriptionally and functionally. This will be extremely valuable for studying DCs in vitro and for further developing autologous DC-based antitumor vaccinations.